Pemberdayaan Masyarakat dalam Pengolahan Sampah Organik Menjadi Produk Bernilai Ekonomis : Pengabdian - Darmin; Juraidin; Mastorat; Erham; Gufran; Juhriati; Jufrin; Christien Gloria Tutu; Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The main problem faced by the Bumi Pajo village community is that durian peel waste, generated from seasonal consumption by the village community, has not been optimally utilized. In developing household products, the community does not yet have the skills and knowledge to process this waste into creative and marketable products, such as durian peel chips, compost materials, or crafts. As a result, the economic potential of this waste is neglected and even causes environmental problems. The implementation method of this community service program starts from an initial survey and mapping of potential partners, technical training, and mentoring the fermentation process of durian peel into vinegar that can be used as a household product or an additive in the food and health sectors. This community service program is directed at education and basic training in processing durian peel waste into vinegar, as well as its use in everyday life. The program also includes training in product packaging, local marketing strategies, and a simple introduction to digital marketing to increase product sales. The results of community service include the processing of durian peels into economically valuable products, such as durian peel chips, organic compost, and home crafts.